Electron-to Hole Transport Change Induced by Solvent Vapor Annealing of Naphthalene Diimide Doped with Poly(3-Hexylthiophene) - Janus, Krzysztof; Danielewicz, Kinga; Chlebosz, Dorota; Goldeman, Waldemar; Kiersnowski, Adam (Frontiers in Chemistry, 2021)
Herein we report on fabrication and properties of organic field-effect transistors (OFETs) based on the spray-coated films of N,N′-dioctyl naphthalene diimide (NDIC8) doped with 2.4 wt% of poly (3-hexylthiophene) (P3HT). OFETs with the untreated NDIC8:P3HT films revealed electron conductivity [μe* = 5 × 10–4 cm2×(Vs)−1]. After the annealing in chloroform vapor the NDIC8:P3HT films revealed the hole transport only [μh* = 0.9 × 10–4 cm2×(Vs)−1]. Due to the chemical nature and energy levels, the hole transport was not expected for NDIC8-based system. Polarized optical- and scanning electron microscopies indicated that the solvent vapor annealing of the NDIC8:P3HT films caused a transition of their fine-grained morphology to the network of branched, dendritic crystallites. Grazing incidence wide-angle X-ray scattering studies indicated that the above transition was accompanied by a change in the crystal structure of NDIC8. The isotropic crystal structure of NDIC8 in the untreated film was identical to the known crystal structure of the bulk NDIC8. After the solvent annealing the crystal structure of NDIC8 changed to a not-yet-reported polymorph, that, unlike in the untreated film, was partially oriented with respect to the OFET substrate.